Achieving food security in a cost effective way: implications of domestic regulation and reform under liberalized trade - Jha, Shikha; Srinivasan, P. V. (International Food Policy Research Institute, 2004)
This study evaluates the domestic and international trade and marketing policies in India and analyzes the effects of deregulating domestic markets and liberalizing external trade on the food grain sector. Historically, India's food policy has involved heavy government intervention in all aspects of the food grain market -- pricing, procurement, stocking, transport and marketing. The Food Corporation of India (FCI) is the principal parastatal agency responsible for marketing food grains within the country and controls nearly 50 percent of the grain markets. An analysis of the performance of the FCI, however, reveals enormous and mounting costs of operations that present a huge financial burden for the Government of India (GOI). This study offers a comparison of the costs and functioning of the FCI with that of private traders, in order to suggest policy options for reform. The results show that private traders operate at costs lower than those incurred by the FCI in both storage and trade, despite several controls and restrictions imposed upon them. Therefore, the finding from this study is that there is a strong case for reform from the efficiency point of view."""" -- From Author's Executive Summary""